IMPLEMENTASI KEBIJAKAN RENTAN ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN HALMAHERA UTARA - BELLA, ANGELA (Sam Ratulangi University, 2013)
Abstract : Administration vulnerable population population population is experiencing barriers in obtaining documents population caused by natural disasters and social disaster victims. In accordance with the results in dapati masi prasurvei many residents in North Halmahera are still experiencing vulnerable population administration. Therefore it is necessary to conduct further research on the